A new deep-sea species of Renella (Amphipoda: Lysianassida: Pakynidae) from the Sea of Okhotsk - Labay, Vjacheslav S. (Zootaxa, 2023)
A new amphipod species, Renella lowryi sp. nov., from the north-eastern slope of the Sea of Okhotsk (Russian Far East) is described. The new species is assigned to the genus Renella Lowry & Stoddart, 2012 because it is similar to the species of this genus in the main characters: in the structure of the mouthparts, the structure of gnathopods 1 and 2, corner of palm of gnathopod 1 with the complex of robust seta, pereopods 3–7, the shape of epimeron 3, uropods and telson. The new species similar to Renella sculptidentata (Ren, 1991) by the structure of antennae 1 and 2, mandible, maxilla 2 and maxilliped, but differs from it by the missing eyes, by the morphology of maxilla 1 outer plate: with 9 setal-teeth in 6/3 arrangement (in R. sculptidentata with 11 setal-teeth in 7/4 arrangement), by the shape of propodus of gnathopod 1 with medially convex anterior margin (in R. sculptidentata anterior margin straight medially), by the shape of propodus of gnathopod 2 with oblique distal margin (in R. sculptidentata distal margin is perpendicular), by the shape of basis of pereopod 5 with rounded posterior wing (in R. sculptidentata posterior wing subrectangular), by the weak armament of the anterior margin of the basis of pereopod 5 and anterior margin of merus of pereopods 5–7 (in R. sculptidentata anterior margins with few long setae), by the length of inner ramus of uropod 3 which subequal to proximal segment of outer ramus in length (in R. sculptidentata inner ramus shorter than proximal segment of outer ramus). Keys to the world species of the genus Renella is provided.